2008
DOI: 10.1523/jneurosci.1083-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Regulates Migration of Olfactory Interneuron Precursors in the Rostral Migratory Stream through Met-Grb2 Coupling

Abstract: The olfactory bulb is one of the few structures in the mammalian forebrain in which continuous neurogenesis takes place throughout life. Neuronal precursors originate from progenitors located in the subventricular zone (SVZ) of the lateral ventricles, move tangentially in chains through the rostral migratory stream (RMS), and reach the olfactory bulb (OB), where they finally differentiate into granule and glomerular interneurons. Multiple molecular factors are involved in controlling the various steps of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 59 publications
3
57
1
Order By: Relevance
“…49,50 Other growth/trophic factors such as hepatocyte growth factor, brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor, and Netrin-1 also show attractant activity for neuroblasts in vitro, although in vivo evidence for their involvement remains to be demonstrated. [51][52][53][54] In the RMS, neuroblasts move inside the glial tube, which is reported to support their long-distance cell migration through intercellular molecular interactions. For example, the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) secreted by migrating neuroblasts is taken up by the RMS astrocytes, leading to negative regulation of the migration speed.…”
Section: Fig 2 Regulation Of Svz Neurogenesis By Wnt Signalingmentioning
confidence: 88%
“…49,50 Other growth/trophic factors such as hepatocyte growth factor, brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor, and Netrin-1 also show attractant activity for neuroblasts in vitro, although in vivo evidence for their involvement remains to be demonstrated. [51][52][53][54] In the RMS, neuroblasts move inside the glial tube, which is reported to support their long-distance cell migration through intercellular molecular interactions. For example, the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) secreted by migrating neuroblasts is taken up by the RMS astrocytes, leading to negative regulation of the migration speed.…”
Section: Fig 2 Regulation Of Svz Neurogenesis By Wnt Signalingmentioning
confidence: 88%
“…Tissue explant cultures were performed as described by Garzotto et al (2008). Briefly, brains were dissected out and cut by Vibratome into 250 ÎŒm thick coronal slices.…”
Section: Organotypic Culturesmentioning
confidence: 99%
“…HGF was previously shown to be involved in interneuron (42) and striatal progenitor cell (43) migration. It was recently shown that HGF promotes migration of rostral migratory stream neuroblasts (44) and that HGF is the factor secreted by glioma to attract neural progenitor cells (45). We asked whether MTP is also involved in NP cell migration stimulated by these factors.…”
Section: Mtp Is Required For Np Cells To Migrate Across Reconstitutedmentioning
confidence: 99%